Factorial Invariance of Self-efficacy in Physical Health Care Scale for Men and Women University Students - Judith M. Rodriguez-Villalobos; Luis H. Blanco Vega; Martin A. Gonzalez; Yunuen Rangel Ledezma (European Scientific Journal, ESJ, 2016)
The present study analyses the psychometric properties of the Selfefficacy in Physical Health Care Scale. The overall sample consisted of 2006 subjects: 902 women and 1104 men, with a mean age of 18.53 years (SD= 1.52) and 18.84 years (SD= 1.55) respectively. The Factorial Psychometric analysis showed that a three-factorial structure (nutrition, physical health and hydration) was viable and adequate for both populations (men and woman) according to the established psychometric requirements when the informers are the students themselves. The results showed that factor structure, factor loadings and intercepts of the instrument could be considered invariant across groups; however, there are differences between groups in favor of men for the means of the nutrition and physical health factors.